2016
DOI: 10.1007/s13402-016-0297-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel strategies for targeting leukemia stem cells: sounding the death knell for blood cancer

Abstract: Background Cancer stem cells (CSCs), also known as tumor-initiating cells (TICs), are characterized by high self-renewal and multi-lineage differentiation capacities. CSCs are thought to play indispensable roles in the initiation, progression and metastasis of many types of cancer. Leukemias are thought to be initiated and maintained by a specific sub-type of CSC, the leukemia stem cell (LSC). An important feature of LSCs is their resistance to standard therapy, which may lead to relapse. Increasing efforts ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 158 publications
(167 reference statements)
0
9
0
Order By: Relevance
“…Leukemia is also known as blood cancer and has a high mortality rate. It is pathologically characterized by the massive proliferation of abnormal hematopoietic stem cells (1,2). Although the precise pathogenesis of leukemia remains to be elucidated, various genetic mutations occurring in response to factors including genetic factors, immune deficiency, toxic agents and the leukosis virus in the process of leukocyte differentiation have been widely accepted as the main causes of leukemia (3).…”
Section: Introductionmentioning
confidence: 99%
“…Leukemia is also known as blood cancer and has a high mortality rate. It is pathologically characterized by the massive proliferation of abnormal hematopoietic stem cells (1,2). Although the precise pathogenesis of leukemia remains to be elucidated, various genetic mutations occurring in response to factors including genetic factors, immune deficiency, toxic agents and the leukosis virus in the process of leukocyte differentiation have been widely accepted as the main causes of leukemia (3).…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of miR-214 decreases the sensitivity of PDAC tumor cells to gemcitabine by inhibiting inhibitor of growth family member 4 (26). Furthermore, the association of certain aberrantly expressed miRNAs with the clinical outcomes of patients with PDAC has been reported in numerous previous studies (2730). For example, elevated miR-21 expression levels are significantly correlated with worse overall survival and progression-free survival in patients with PDAC (31).…”
Section: Introductionmentioning
confidence: 58%
“…Previous studies have revealed that chidamide and DNA damaging agents can synergistically promote apoptosis in relapsed and refractory acute myeloid leukemia cells and reduce tumor burden in patients ( 39 ), and that VPA and bortezomib cooperate to induce pancreatic cancer cell death ( 40 ). Although chidamide and VPA did not inhibit MM cell proliferation and promote apoptosis, as expected, in the short term (6 h), which may be associated with the complexity of cell proliferation and development mechanisms, the rapid inhibition of NF-κB may inhibit the continued growth of MM cells in the early stages.…”
Section: Discussionmentioning
confidence: 99%